Uptake of Small EVs by Skeletal Muscle Myoblasts In Vitro and Subsequent Myogenic Response to Cargo - Dlamini, Nonhle (Stellenbosch : Stellenbosch University, 2026)
Thesis (MSc)--Stellenbosch University, 2026.